Common and uncommon features of focal splenic lesions on contrast-enhanced ultrasound: a pictorial review - Zavariz,Julia D. (2017)
Abstract The characterization of focal splenic lesions by ultrasound can be quite challenging. The recent introduction of contrast-enhanced ultrasound (CEUS) has come to play a valuable role in the field of imaging splenic pathologies, offering the possibility of an ionizing radiation-free investigation. Because CEUS has been incorporated into everyday clinical practice, malignant diseases such as focal lymphomatous infiltration, metastatic deposits, benign cysts, traumatic fractures, and hemangiomas can now be accurately depicted and characterized without the need for further imaging. More specifically, splenic traumatic fractures do not require additional imaging by computed tomography (with ionizing radiation exposure) for follow-up, because splenic fractures and their complications are safely imaged with CEUS. In the new era of CEUS, more patients benefit from radiation-free investigation of splenic pathologies with high diagnostic accuracy.